The Medicalisation of Childbearing - Alys Einion (The Social Context of Birth, 2017)
The medicalization of a normal body function is linked to the historical control of women's bodies, and reproduction, by a patriarchal social and medical system. The impact of this on women's experiences of pregnancy and birth in the current context is discussed.